Not 'Dead Letters', Just 'Blind Eyes': The Europeanisation of Drinking Water Risk Regulation in Estonia and Lithuania. (February 2015) - Orru, Kati; Rothstein, Henry
This paper draws on a detailed empirical study of the implementation of the EU's Drinking Water Directive in Estonia and Lithuania in order to understand the factors shaping the Europeanisation of risk regulation regimes in Eastern accession states. Adopting a 'whole-regime' methodological approach, the paper explores the key drivers and constraints shaping the transposition as well as the practical implementation of the law. The study shows how 'conditionality' pressures to adopt the EU acquis in order to access European economic and financial support networks have reinforced, rather than overcome, historically entrenched regulatory cultures. Going beyond well-known typologies of Europeanisation, the paper identifies a distinctive 'blind-eye' style of Europeanisation in which conditionality pressures have favoured selective compliance with ill-suited EU rules at the expense of tackling significant drinking water risk problems. The paper shows how such symbolic policy practices have been shaped through a combination of the countries' shared Soviet legacies of elite-centred and legalistic governance cultures, the active coping strategies of street-level inspectors, as well as wider sociopolitical contexts that have limited the impact of civil society actors such as scientists, NGOs, and the general public in strengthening risk regulation in the Baltic states. The paper also shows, however, that the different post-Soviet ideological orientations and administrative reform programmes of Eastern European accession states can override their common Soviet legacies and lead to significant national variation in risk regulation processes and outcomes.